2008
DOI: 10.1111/j.1557-9263.2008.00170.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling distributions of disjunct populations of the Sierra Madre Sparrow

Abstract: Sierra Madre Sparrows (Xenospiza baileyi) are among the least known of all bird species in Mexico. Recent surveys have discovered previously unknown populations and the current known distribution of Sierra Madre Sparrows consists of two populations separated by >800 km. We used available distributional information to develop ecological niche models that (1) predict much of the distribution potential of the species, (2) establish that the broad disjunction separating the two populations has ecological correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 29 publications
1
29
0
3
Order By: Relevance
“…First, X. baileyi populations show no differences in morphology, plumage coloration or behavior between the SMO and TVB populations (Dickerman et al 1967), leading to the species currently being considered monotypic (contrary to the earlier suggestion by Pitelka 1947, which was based on inadequate sampling). Secondly, with respect to ecological equivalence, Rojas-Soto et al (2008) concluded that the TVB and SMO populations are found in similar ecological environments based on ecological niche models.…”
Section: Delimitation Of Management Units and Management Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…First, X. baileyi populations show no differences in morphology, plumage coloration or behavior between the SMO and TVB populations (Dickerman et al 1967), leading to the species currently being considered monotypic (contrary to the earlier suggestion by Pitelka 1947, which was based on inadequate sampling). Secondly, with respect to ecological equivalence, Rojas-Soto et al (2008) concluded that the TVB and SMO populations are found in similar ecological environments based on ecological niche models.…”
Section: Delimitation Of Management Units and Management Strategymentioning
confidence: 99%
“…A decade ago it was estimated that more than 50% of suitable habitat had disappeared in the previous 10 years (Cabrera 1999;González 2000), and the factors leading to this decrease have not diminished. The current populations in the TVB and SMO occur in areas with very similar ecological conditions (Rojas-Soto et al 2008), despite being separated by more than 800 km.…”
Section: Introductionmentioning
confidence: 99%
“…SDM has been applied to address conservation issues including evaluating species representation within natural protected area networks (Nóbrega and De Marco 2011;Bosso et al 2013) and identifying optimal values of key environmental variables that favor species survival at broad scales (Rojas-Soto et al 2008). Species potential distribution models have also been used to support the drawing of geographic limits for species considered taxonomically problematic (Raxworthy et al 2007) and to understand speciation patterns (Peterson et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying such gaps should ensure that most of the remnant patches of humid montane forest that potentially still host a Doliornis cotinga can be identified and considered in conservation planning. Our study illustrates how species distribution modeling could be used for assessing the distribution and conservation status of rare species known only from scattered, opportunistic records collected by field ornithologists (Bourg et al 2005, Peterson and Papes 2007, Rojas‐Soto et al 2008, Marini et al, 2010).…”
mentioning
confidence: 99%
“…This feature is particularly useful for species known from a limited number of locations, including poorly detectable, inconspicuous or low‐density species, species in remote, poorly investigated habitats, or recently discovered species (Raxworthy et al 2003, Engler et al 2004, Franklin et al 2009, Marini et al, 2010). These models are increasingly used by field ornithologists to exploit bird distributional data (e.g., Rojas‐Soto et al 2008, Henry and Aznar 2009).…”
mentioning
confidence: 99%